Performance of tests to prevent cervical cancer: promoting health nursing home - Costa, Camila Chaves da; Freitas, Lydia Vieira; Dias, Levânia Maria Benevides; Lima, Thaís Marques; Damasceno, Ana Kelve de Castro; Pinheiro, Ana Karina Bezerra (Rev Rene, 2010)
A growing number of elderly women sexually active, requiring the attention of health professionals to exercise their sexuality in a healthy way. Aimed at learning about the habits for the prevention of cervical cancer in elderly institutionalized in Fortaleza. Study a quantitative approach, with a descriptive and cross-section. Held in a nursing home, with 46 and 26 elderly. Data collection was by an instrument of objective questions in the month of April 2008. Found low education, a minority were married, 21.7% had never performed the Pap smear, 63.9% contained no regularity in the examinations and none had cancer. Some factors hinder the implementation of strategies for Health Education: low educational level, the proximity of death. But we have to invest in activities that encourage this population in the areas of their lives.